The Fragility of Meaningful Law Enforcement in Indonesia Viewed from A Progressive Law Perspective - Agahirber; Sunarso; Irwan (Universitas Muhammadiyah Yogyakarta, 2025)
Through a holistic approach to the conceptualization of progressive law, this research aims to analyze and provide a comprehensive view of the fragile meaning of law in Indonesia after the MKMK decision Number 2/MKMK/L/11/2023 as viewed from progressive law. This research is normative or dogmatic legal research which refers to two data sources: primary and secondary. The primary source refers to MKMK Decision Number 2/MKMK/L/11/2023. Furthermore, secondary sources include law books, law research results, and the views of experts, especially the Progressive Law paradigm by Prof. Satjipto Rahardjo. The research results show that MKMK Decision Number 02/MKMK/L/11/2023 marks the point of fragility of the meaning of law in Indonesia based on violations of the Constitutional Court Judge's Code of Ethics and Behavior by Anwar Usman as Chief Judge of the Constitutional Court at the time of ratification of Constitutional Court Decision Number 90/PUU -XXI/2023 which is full of personal interests. The “nemo judex in causa sua” principle in law indicates that a judge cannot handle cases involving his interest. That is important to revitalize the meaning of law by promoting progressive law that prioritizes morality to minimize ethical defects in the rule of law in the future.